Ubiquitin‐specific protease 22 promotes tumorigenesis and progression by an FKBP12/mTORC1/autophagy positive feedback loop in hepatocellular carcinoma - Qianwei Ye; Wei Zhou; Shengjun Xu; Qingyang Que; Qifan Zhan; Lincheng Zhang; Shusen Zheng; Sunbin Ling; Xiao Xu (MedComm, 2023)
Abstract Ubiquitin‐specific protease 22 (USP22) has been identified as a potential marker for cancer stem cells in hepatocellular carcinoma (HCC). It can promote HCC stemness, which is considered a driver of tumorigenesis. Here, we sought to determine the role of USP22 in tumorigenesis, elucidate its underlying mechanism, and explore its therapeutic significance in HCC. As a result, we found that tissue‐specific Usp22 overexpression accelerated tumorigenesis, whereas Usp22 ablation decelerated it in a c‐Myc/NRasGV12‐induced HCC mouse model and that the mammalian target of rapamycin complex 1 (mTORC1) pathway was activated downstream. USP22 overexpression resulted in increased tumorigenic properties that were reversed by rapamycin in vitro and in vivo. In addition, USP22 activated mTORC1 by deubiquitinating FK506‐binding protein 12 (FKBP12) and activated mTORC1, in turn, further stabilizing USP22 by inhibiting autophagic degradation. Clinically, HCC patients with high USP22 expression tend to benefit from mTOR inhibitors after liver transplantation (LT). Our results revealed that USP22 promoted tumorigenesis and progression via an FKBP12/mTORC1/autophagy positive feedback loop in HCC. Clinically, USP22 may be an effective biomarker for selecting eligible recipients with HCC for anti‐mTOR‐based therapy after LT.